Nanoscale interface for organic electronics - Iwamoto, Mitsumasa; Kwon, Young-Soo; Lee, Takhee (World Scientific, 2011)
The scope of this book will be focused on the interface issues and problems in organic materials as electronic device applications. The organic material electronics is a rapidly progressing field for potential applications in flexible field effect transistors, plastic solar cells, organic luminescent devices, etc. However, the performance of these organic devices is still not sufficient. To enhance the understanding and practical applications of organic devices, we need to understand the fundamental organic device physics which is somewhat different from the conventional inorganic device physics. This book will discuss the detailed progress in these topics.
Keywords: Organic electronics.; Nanoelectronics.; elektronické knihy; electronic books